Asymptotic Stability of an Abstract Delay Functional-Differential Equation - Tchuenche, J. M. (Nonlinear Analysis: Modelling and Control, 2006)
We study the exponential asymptotic stability of an abstract functional-differential equation with a mixed type of deviating arguments, namely: c which might represent the gestation period of the population and r(u(t)), a suitably defined function. The equation is reduced to its equivalent integral form and solved via Laplace transform method. An interesting connection of our study is with generalizations of populations with potentially complex (chaotic) dynamics.
Keywords: stability; resolvent; gestation; delay differential equation